INFECCIÓN POR Leishmania sp. EN CANINOS DEL DISTRITO DE PAMPAS GRANDE, ANCASH - Medina R., Guicela (2002)
The Andean Leishmaniasis locally known as "uta" is the most frequent type of cutaneous leishmaniasis in Peru. Ancash is an endemic region and Pampas Grande is the district with higher incidence of the disease in humans in the province of Huaraz in 1998. The objective of this research was to determine the presence of Leishmania sp. infection in domestic dogs in the district of Pampas Grande. A total of 83 dogs distributed in seven villages were sampled in August-September 2000. Ali samples were submitted to three laboratory analyses for the detection of cutaneous leishmaniasis: Giemsa smears, antibody detection in serum through indirect immunofluoresence (IFI), and immunoleish skin test (IDR). The results indicate 3.6% incidence while using Giemsa smears and IFI, whereas 4.8% while using IDR. The study showed that Leishmania sp. infection is present in at least 5.4% of the canine domes tic dog population in Pampas Grande.